Avaliação do efeito da dexametasona e da nimesulida na quimionecrose do osso mandibular induzida por ácido zoledrônico em ratos - Oliveira, Camila Carvalho de (2015)
Bisphosphonate-associated osteonecrosis of the jaw (OMB) has no defined pathophysiology, but has been linked to proinflammatory events. Dexamethasone (DEX) and nimesulide (NIM), steroidal and nonsteroidal anti-inflammatory agents (AIs), respectively, reduce inflammation mediators. The aim of this study was to evaluate the effect of dexamethasone and nimesulide in the chemonecrosis on jawbone associated with zoledronic acid (AZ) in rats. OMB was induced in male Wistar rats (n=40) by AZ administration and by extraction of the first left molar (OMB groups). DEX (0.04, 0.4, 4 mg/kg) or saline was administered, by gavage, 24 h, or NIM (10.3 mg/kg), 24 h and 12 h before each infusion of ZA, for eight weeks. Controls groups (n=40) received just treatment with AIs or saline. The body mass variation and hematological analyses were conducted weekly. Surgical time and number of fractured roots were measured to assess the difficulty of dental extraction. After the sacrifice (day 70), jaws and organs were excised. Digital x-rays of the jaws were made to measure the suggestive radiolucent area of necrosis and, later, histological slides were made (hematoxylin-eosin) to histomorphometric analysis. Kidney, liver, spleen and stomach were weighed, to express the organ index, and, after, these were submitted to histological processing for histopathological analysis. The group OMB DEX 4 mg/kg presented higher surgical time compared to saline. Radiographic analysis showed higher radiolucent area in the OMB groups compared to controls (p<0.05). Histomorphometric analysis revealed devitalized bone with of empty osteocytes lacunae, apoptotic osteoclasts, bacterial colonies and inflammatory infiltrate in the animals from AZ, whereas in the control animals, was visualized healing and new bone formation. The OMB DEX 0.4 and 4 mg/kg groups had the greatest number of bacterial colonies (p <0.05) and neutrophils when they were compared with the saline-OMB. Already on the OMB-Nimesulide group was seen less inflammatory infiltrate (p <0.05). The OMB groups showed anemia associated with leukocytosis, which was reduced by DEX administration. VMC analysis revealed lower weight of rats OMB treated with AIs compared to controls on day 13 (p <0.05). Treatments with DEX 4 mg/kg and NIM, associated or not to AZ, seemed cause worse damage in the stomach and liver. In the kidney, treatment with AI in OMB animals was observed numerous hyaline-cylinders. In the spleen, DEX caused atrophy of the white pulp, associated with splenic index. Thus, treatment with AIs was not effective in prevention OMB. AZ infusion was associated with the occurrence of anemia, leukocytosis, and weight loss in 13 days.